Freshwater mussel populations in Pacific Coast Watersheds (Oregon, USA): occurrence, condition, habitat, and fish species overlap - Kaegan Scully-Engelmeyer; Emilie Blevins; Elise F. Granek; Ron Constable (Hydrobiologia, 2023)
In the western US, freshwater mussels (Order Unionida) contribute valuable ecosystem functions to riverine systems, yet have declined across their range following widespread degradation of freshwater habitat and parallel declines in salmonids, host fish for larval western pearlshell mussels ( Margaritifera falcata ). The status of M. falcata populations is of particular conservation interest in isolated coastal watersheds given unique freshwater mussel-host fish relationships. To understand M. falcata population ecology in Oregon’s coastal watersheds, we analyzed stream survey data on presence/absence of mussels collected over a recent eleven-year period, explored co-varying habitat characteristics, and summarized mussel distribution and host fish co-occurrence. We also collected M. falcata and compared condition indices among eight locations. Naïve occupancy in surveyed areas was 12.3%, about half of predicted occupancy ( ψ = 0.24, CI 0.19–0.31) based on modeling repeated visits over a ten year assumed closed period. Mussel occupancy was correlated with reach-scale habitat variables, and the probability of mussel observations was positively correlated with presence of coho ( Oncorhynchus kisutch ) salmon. Condition varied significantly among locations. Spatial relationships between existing mussel distribution, host species, and habitat variables answer questions about coastal freshwater mussel populations, as well as serve to identify priorities for further research and population assessment.

First report of watermelon crinkle leaf associated virus-1 (WCLaV-1) in watermelon (Citrullus lanatus) in Australia - S. Mulholland; O. Wildman; W. M. Kinoti; F. Constable; A. Daly; L. Tesoriero; S. Maina; T. A. Chapman (Journal of Plant Pathology, 2022)
Surveys of key cucurbit production regions in New South Wales, Australia were undertaken to catalogue the diversity of viral pathogens affecting field grown cropping systems. Analysis of the collected isolates confirmed a detection of watermelon crinkle leaf associated virus-1 (WCLaV-1) in watermelon constituting the first report of WCLaV-1 in Australia. A mixed infection of WCLaV-1 and watermelon mosaic virus (WMV) was also detected constituting the first report of this type of pathogen combination.

Combating ecosystem collapse from the tropics to the Antarctic - Dana M. Bergstrom; Barbara C. Wienecke; John van den Hoff; Lesley Hughes; David B. Lindenmayer; Tracy D. Ainsworth; Christopher M. Baker; Lucie Bland; David M. J. S. Bowman; Shaun T. Brooks; Josep G. Canadell; Andrew J. Constable; et al. (Global Change Biology, 2021)
Globally, collapse of ecosystems—potentially irreversible change to ecosystem structure, composition and function—imperils biodiversity, human health and well‐being. We examine the current state and recent trajectories of 19 ecosystems, spanning 58° of latitude across 7.7 M km 2 , from Australia's coral reefs to terrestrial Antarctica. Pressures from global climate change and regional human impacts, occurring as chronic ‘presses’ and/or acute ‘pulses’, drive ecosystem collapse. Ecosystem responses to 5–17 pressures were categorised as four collapse profiles—abrupt, smooth, stepped and fluctuating. The manifestation of widespread ecosystem collapse is a stark warning of the necessity to take action. We present a three‐step assessment and management framework (3As Pathway Awareness , Anticipation and Action ) to aid strategic and effective mitigation to alleviate further degradation to help secure our future.

Global Drivers on Southern Ocean Ecosystems: Changing Physical Environments and Anthropogenic Pressures in an Earth System - Simon A. Morley; Doris Abele; David K. A. Barnes; César A. Cárdenas; Cedric Cotté; Julian Gutt; Sian F. Henley; Juan Höfer; Kevin A. Hughes; Stephanie M. Martin; Carlos Moffat; Marilyn Raphael; et al. (Frontiers in Marine Science, 2020)
The manuscript assesses the current and expected future global drivers of Southern Ocean (SO) ecosystems. Atmospheric ozone depletion over the Antarctic since the 1970s, has been a key driver, resulting in springtime cooling of the stratosphere and intensification of the polar vortex, increasing the frequency of positive phases of the Southern Annular Mode (SAM). This increases warm air-flow over the East Pacific sector (Western Antarctic Peninsula) and cold air flow over the West Pacific sector. SAM as well as El Niño Southern Oscillation events also affect the Amundsen Sea Low leading to either positive or negative sea ice anomalies in the west and east Pacific sectors, respectively. The strengthening of westerly winds is also linked to shoaling of deep warmer water onto the continental shelves, particularly in the East Pacific and Atlantic sectors. Air and ocean warming has led to changes in the cryosphere, with glacial and ice sheet melting in both sectors, opening up new ice free areas to biological productivity, but increasing seafloor disturbance by icebergs. The increased melting is correlated with a salinity decrease particularly in the surface 100 m. Such processes could increase the availability of iron, which is currently limiting primary production over much of the SO. Increasing CO 2 is one of the most important SO anthropogenic drivers and is likely to affect marine ecosystems in the coming decades. While levels of many pollutants are lower than elsewhere, persistent organic pollutants (POPs) and plastics have been detected in the SO, with concentrations likely enhanced by migratory species. With increased marine traffic and weakening of ocean barriers the risk of the establishment of non-indigenous species is increased. The continued recovery of the ozone hole creates uncertainty over the reversal in sea ice trends, especially in the light of the abrupt transition from record high to record low Antarctic sea ice extent since spring 2016. The current rate of change in physical and anthropogenic drivers is certain to impact the Marine Ecosystem Assessment of the Southern Ocean (MEASO) region in the near future and will have a wide range of impacts across the marine ecosystem.

A new blunervirus infects tomato crops in Italy and Australia - M. Ciuffo; W. M. Kinoti; A. Tiberini; M. Forgia; L. Tomassoli; F. E. Constable; M. Turina (Archives of Virology, 2020)

Identification and complete genome analysis of a virus variant or putative new foveavirus associated with apple green crinkle disease - D. James; A. Varga; G. D. Jesperson; M. Navratil; D. Safarova; F. Constable; M. Horner; K. Eastwell; W. Jelkmann (Archives of Virology, 2013)

A survey of key Australian pome fruit growing districts for exotic and endemic pathogens - F. E. Constable; P. A. Joyce; B. C. Rodoni (Australasian Plant Pathology, 2007)

Genetic variability amongst isolates of Australian grapevine phytoplasmas - F. E. Constable; R. H. Symons (Australasian Plant Pathology, 2004)